Experiment and Finite Element Research on Mechanical Performance of Thin-Walled Steel–Wood Composite Columns Under Eccentric Compression - Yangfa Zhu; Jianhua Shao; Anxiang Feng; Xianglan Li; Zhanguang Wang; Hongxuan Xu; Jiajun Gao; Boshi Ma (Buildings, 2025)
In order to conduct an in-depth and exhaustive investigation into the mechanical properties of steel tubes filled with wood, a thin-walled steel–wood composite column was elaborately designed. The damage progression, failure mode, and mechanical performance of this column under eccentric compression were systematically investigated through both experimental research and finite element simulations. The impacts of different numbers of bolts on the mechanical properties of the composite column were minutely analyzed, and the test results of composite columns were compared with the pure steel pipe column under the same experimental conditions. It was clearly observed that the pure thin-walled steel pipe specimen was highly susceptible to elastic instability under eccentric compression, and the high-strength and high-ductility potential of structural steel was not fully developed. However, after filling with wood and applying bolt restraints, the greater the number of bolts in the specimen of thin-walled steel–wood composite column under the identical eccentricity condition, the higher the ultimate load-bearing capacity. Specifically, the ultimate load-bearing capacity of the columns filled with wood increased by 77.78–114% in comparison with that of the pure steel pipe column. Through a meticulous comparison between the test and finite element analysis results, the error was ascertained to be in the range of 4.9–11.1%. In addition, filling the thin-walled steel tube with wood and restraining it with bolts can effectively enhance the lateral deformation resistance of the specimens, and the reduction rate of lateral deflection exceeded 50%. Moreover, the greater the number of filling bolts, the smaller the strain of components subjected to the eccentric compression occurred, and the better the mechanical properties.